Mice with cisplatin and oxaliplatin-induced painful neuropathy develop distinct early responses to thermal stimuli - Ta Lauren E; Low Philip A; Windebank Anthony J (SAGE Publishing, 2009)
Abstract Background Cisplatin has been in use for 40 years for treatment of germ line and other forms of cancer. Oxaliplatin is approved for treatment of metastatic colorectal cancer. Thirty to forty percent of cancer patients receiving these agents develop pain and sensory loss. Oxaliplatin induces distinctive cold-associated dysesthesias in up to 80% of patients. Results We have established mouse models of cisplatin and oxaliplatin-induced neuropathy using doses similar to those used in patients. Adult male C57BL6J mice were treated with daily intraperitoneal injection for 5 days, followed by 5 days of rest, for two cycles. Total cumulative doses of 23 mg/kg cisplatin and 30 mg/kg oxaliplatin were used. Behavioral evaluations included cold plate, von Frey, radiant heat, tail immersion, grip strength and exploratory behavior at baseline and at weekly intervals for 8 weeks. Following two treatment cycles, mice in the cisplatin and oxaliplatin treatment groups demonstrated significant mechanical allodynia compared to control mice. In addition, the cisplatin group exhibited significant thermal hyperalgesia in hind paws and tail, and the oxaliplatin group developed significant cold hyperalgesia in hind paws. Conclusion We have therefore established a model of platinum drug-induced painful peripheral neuropathy that reflects the differences in early thermal pain responses that are observed in patients treated with either cisplatin or oxaliplatin. This model should be useful in studying the molecular basis for these different pain responses and in designing protective therapeutic strategies.